Skype hacks - Sheppard, Andrew, 1961- (O'Reilly, 2005)
If you've heard about Skype--and who hasn't with all the recent media attention devoted to internet telephone services--chances are you've been mighty tempted to try it out. Skype Hacks tells you what all the Skype hype is about, explains the basics, and shows you more than 100 clever tips and tricks for tweaking and tuning Skype to make it do just what you want and more. Millions of people (48 million and counting, in fact) have opted for Skype, which uses peer-to-peer (P2P) technology to turn any PC, Mac, or Pocket PC into a telephone. Skype offers free calls between computers and extremely cheap calls to "old-fashioned" phone numbers (landlines and mobile phones). The sound quality is excellent, and end-to-end encryption means the connection is private and secure. But if you really know what you're doing, Skype can accomplish a whole lot more than that. Software developer and author Andrew Sheppard recently converted his entire house to Skype and uses it for all his personal and business calls, even when he's traveling. In Skype Hacks, he shows you how to do things with the technology that even the engineers at Skype probably never intended. Skype Hacks shows you how to: Get started with Skype Figure out how much money you're saving and maximize your savings Cut the ties to your old phone company Optimize your Skype configuration Integrate Skype with desktop tools like Microsoft Office and your web browser Set up a Skype-based call center The book offers ideas for creating and organizing a contacts list, using Skype to transfer files, taking advantage of chat and voicemail capabilities, turning a PDA into a mobile phone, and automating Skype for even greater efficiency. So whether you'd simply like to give Skype a trial run, you want new Skype ring tones and fun on-hold music, or you're considering wiring your home with Skype to get rid of "regular" phone service altogether, Skype Hacks is your ideal guide.